Efficacy of Honey on Sex Reversal of Guppy (Poecilia reticulata Peters) - Soelistyowati, D.T.; Martati, E.; Arfah, H. (Indonesian Society of Scientific Aquaculture (ISSA), 2007)
This study was performed to determine effectiveness of honey on sex reversal of guppy. Guppy broodstock was dipped on 1 L of water containing 0, 20, 40 or 60 mL of honey, for 10 hours. Sex identification was carried out by morphologically and histological method. The results of study show that percentage of male progeny tends to increase by increasing the dose of honey used. Higher percentage of male fish is obtained by the dose of 60 ml/L (59.5% male), about 2.4 fold higher than that of control (24.3% male). Dipping of honey has no effect on survival of broodstock and larvae. Keywords: honey, sex reversal, monosex, Poecilia reticulata ABSTRAK Penelitian ini dilakukan untuk mengetahui efektivitas madu dalam pengarahan diferensiasi kelamin ikan gapi. Induk ikan gapi direndam dalam 1 L air yang mengandung 0, 20, 40 atau 60 mL madu, selama 10 jam. Jenis kelamin ikan gapi diidentifikasi secara morfologis dan metode histologi. Hasil penelitian menunjukkan bahwa persentase anak ikan gapi jantan cenderung meningkat seiring dengan peningkatan dosis madu yang diberikan. Persentase tertinggi ikan gapi jantan diperoleh pada perlakuan 60 mg/l media (59,5%), sekitar 2,4 kali lebih tinggi daripada kontrol (24,3%). Perendaman dengan madu terbukti tidak mempengaruhi tingkat kelangsungan hidup induk dan larva. Kata kunci: madu, pengarahan kelamin, monoseks, Poecilia reticulata